HUBUNGAN GANGGUAN FUNGSI FISIK DAN DUKUNGAN KELUARGA DENGAN HARGA DIRI LANSIA DI PUSKESMAS PUTRI AYU KOTA JAMBI TAHUN 2019 - Firza Fachrunnisa; Daryanto Daryanto; Vevi Suryenti Putri (Jurnal Akademika Baiturrahim Jambi, 2019)
Health problems often experienced by the elderly are one of the psychological problems of self-esteem. Self-esteem in the elderly that is not treated will cause low self-esteem problems, factors that affect self-esteem are impaired physical function and low family support. Problems that are often experienced by the elderly are impaired physical function and lack of family support. This study aimed to determine the correlation of physical function impairment and family support with elderly self-esteem at the public health center Putri Ayu Jambi city year 2019. This is a quantitative research by using cross sectional design. Populations were all elderly aged 60-70 who visited at the public health center Putri Ayu Jambi city year 2018 as many as 5655 people. Samples were 95 respondents, it used accidental sampling technique. This study was conducted from May 16th – 29th 2019. The collecting of data used questionnaire. It analyzed as univariate and bivariate by using chi-square test.  The findings indicated that as many as 65.3% have good family support for the elderly, as many as 67.4% elderly experience mild physical impairment and as many as 38.9% the elderly have low self-esteem. On the statistical test indicated that there is significant correlation between physical function impairment (p-value 0.000) and family support (p-value 0.007) with elderly self-esteem at the public health center Putri Ayu Jambi city year 2019. It is expected to health personnel at the public health center to increase counseling about elderly health and self-esteem and also increase counseling to elderly families about family support needed by the elderly, especially about physical changes for the elderly, praise for the elderly, elderly needs and health conditions of the elderly.